Exploring Effects and Mechanism of Ingredients of Herba Epimedii on Osteogenesis and Osteoclastogenesis In Vitro - Song, Lei; Zhou, Yating; Qu, Lin; Wang, Dongyu; Diao, Xinyue; Zhang, Xiaoying; Zhai, Yuxia; Zhang, Yue; Yu, Yingli; Zhou, Kun (Combinatorial Chemistry & High Throughput Screening, 2024)
Background Herba Epimedii, a commonly used traditional herb, has been proven effective in ameliorating osteoporosis. However, the active ingredients and potential mechanism need further exploration. Objective To screen active ingredients of Herba Epimedii with the effect of ameliorating osteoporosis and to explore their potential mechanisms. Methods TCMSP and Swiss Target Prediction were applied to collect the ingredients of Herba Epimedii and their targets. UniProt, GeneCards, TTD, DisGeNET, and OMIM were adopted to search osteoporosis-related genes. STRING and DAVID were used to perform enrichment analysis. Effects of screened ingredients were evaluated on MC3T3-E1 cells and RAW264.7 cells, respectively. Results Eleven ingredients were screened by Network Pharmacology. They exerted a promoting effect on MC3T3-E1 cells (10-9-10-5 M). The ingredients didn’t significantly affect ALP activity and osteoblastogenesis-related genes. Baohuoside 1, Sagittatoside B, Chlorogenic acid, Cryptochlorogenic acid, and Neochlorogenic acid significantly increased calcium depositions. The ingredients didn’t exhibit a dose-dependent inhibition or promotion on RAW264.7 cells. Baohuoside 1, Sagittatoside B, Neochlorogenic acid, Cryptochlorogenic acid, Icariin, Epimedin A, Chlorogenic acid, Sagittatoside A, and Epimedin C suppressed the level of TRACP. Baohuoside 1, Sagittatoside B, Cryptochlorogenic acid, Neochlorogenic acid, Chlorogenic acid, Sagittatoside A, and Icariin decreased the number of multinucleated osteoclastic cells. Baohuoside 1, Sagittatoside B, and Cryptochlorogenic acid could significantly inhibit MMP-9 expression. Conclusion Neochlorogenic acid, Sagittatoside B, Chlorogenic acid, and Cryptochlorogenic acid promoted MC3T3-E1 differentiation, among which Neochlorogenic acid showed significant promotion in viability, mineralization, and OPN expression. Baohuoside 1, Sagittatoside B, Cryptochlorogenic acid, Neochlorogenic acid, Chlorogenic acid, and Icariin inhibited RAW264.7 differentiation, among which Baohuoside 1 showed significant inhibition on TRACP, multinucleated osteoclastic cells number and MPP-9 expression. The mechanism might relate to the FoxO signaling pathway, MAPK signaling pathway, and TNF signaling pathway.
Keywords: epimedin